In ovo Feeding of L-Leucine Improves Antioxidative Capacity and Spleen Weight and Changes Amino Acid Concentrations in Broilers After Chronic Thermal Stress - Han, Guofeng; Cui, Yangyang; Shen, Dan; Li, Mingyang; Ren, Yu; Bungo, Takashi; Chowdhury, Vishwajit S.; Li, Yansen; Li, Chunmei (Frontiers in Veterinary Science, 2022)
L-Leucine (L-Leu) was demonstrated to confer thermotolerance by in ovo feeding in broiler chicks and chickens in our previous studies. However, the L-Leu-mediated roles in recovering from the detrimental effects of heat stress in broilers are still unknown. This study aimed to investigate the effects of L-Leu in ovo feeding on the growth performance, relative weight of organs, serum metabolites and antioxidant parameters, and gene expression profiles in broiler chickens after chronic heat stress. Fertilized broiler eggs (Ross 308) were subjected to in ovo feeding of sterile water (0.5 mL/egg) or L-Leu (69 µmol/0.5 mL/egg) on embryonic day 7. After hatching, the male chicks were separated and used for the current study. All chickens were subjected to thermal stress exposure from 21 to 39 days of age and one week of recovery from 40 to 46 days of age. The results showed that in ovo feeding of L-Leu did not affect the body weight gain or relative weight of organs under chronic heat stress; however, the serum glutathione peroxidase was significantly increased and serum malondialdehyde was significantly decreased by L-Leu at 39 days of age. After one week of recovery, in ovo feeding of L-Leu significantly improved the relative spleen weight at 46 days of age. Subsequent RNA-seq analysis in the spleen showed that a total of 77 significant differentially expressed genes (DEGs) were identified, including 62 upregulated DEGs and 15 downregulated DEGs. Aspartic-type endopeptidase and peptidase activities were upregulated after recovery in the L-Leu group. The expression of genes related to B cell homeostatic proliferation and vestibular receptor cell differentiation, morphogenesis and development was downregulated in the L-Leu group. Moreover, the concentrations of serum catalase, total antioxidative capacity, isoleucine and ammonia were significantly decreased by L-Leu in ovo feeding after recovery. These results suggested that L-Leu in ovo feeding promoted the recovery of antioxidative status after chronic heat stress in broiler chickens.